Pharmacy Leadership and Management module: An evaluation of the student experience and its perceived usefulness for future employment - Boyd, Matthew; Solanki, Vibhu; Anderson, Claire; Sonnex, Kimberley; Brydges, Sarah (2017)
Background: Pharmacy Leadership and Management is a 12-day, final-year synoptic experiential learning simulation. Student teams of six run a primary care-based pharmacy business and are presented with approximately 180 scenarios and over 400 medicines-based exercises. This module is based on the successful model created by the GIMMICS consortia of universities. Aims: To evaluate the acceptability and perceived usefulness to students and their future employment. Method: An online 82-item questionnaire was sent to all 221 students on the module comprising open and closed questions about their module experiences. Two reminders were sent. Analysis consisted of frequency counts and percentages. Results: Sixty-five percent of students completed the survey (n=143). Ninety-two percent said the module challenged them (n=132/143). Eighty-nine percent said it made them more confident talking to patients (n=127/143); 84% reported that their team-working skills improved as the module progressed (n=110/131). Eighty nine percent of students stated that they thought the module consolidated their learning across the degree (n=117/131). Despite the nature of the module, over half felt that the business skills would not be useful to their future career (55%, n=71/131). Conclusion: This new module has assisted students to develop themselves by challenging them and assisting to consolidate their team-working skills. Despite the importance of understanding business and management, students still appear to lack appreciation of this topic, perhaps due to lack of practice exposure in the course. This is the first year the module has run and we will be following up with the now recent graduates to evaluate the module impact on the next stages of their career.